If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (ab + x) + bc = ad Remove parenthesis around (ab + x) ab + x + bc = ad Reorder the terms: ab + bc + x = ad Solving ab + bc + x = ad Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1ad' to each side of the equation. ab + bc + -1ad + x = ad + -1ad Reorder the terms: ab + -1ad + bc + x = ad + -1ad Combine like terms: ad + -1ad = 0 ab + -1ad + bc + x = 0 Add '-1bc' to each side of the equation. ab + -1ad + bc + -1bc + x = 0 + -1bc Combine like terms: bc + -1bc = 0 ab + -1ad + 0 + x = 0 + -1bc ab + -1ad + x = 0 + -1bc Remove the zero: ab + -1ad + x = -1bc Add '-1x' to each side of the equation. ab + -1ad + x + -1x = -1bc + -1x Combine like terms: x + -1x = 0 ab + -1ad + 0 = -1bc + -1x ab + -1ad = -1bc + -1x Reorder the terms: ab + -1ad + bc + x = -1bc + bc + -1x + x Combine like terms: -1bc + bc = 0 ab + -1ad + bc + x = 0 + -1x + x ab + -1ad + bc + x = -1x + x Combine like terms: -1x + x = 0 ab + -1ad + bc + x = 0 The solution to this equation could not be determined.
| (x)+(x+8)+(x+12)=119 | | .75x+12=x+8 | | 3/4x+12=x+8 | | (x)+(x+8)+(x+12)=19 | | mn+x=mk | | (1/6-4/x)/(7/10+6/x^2) | | 3x-16=5x-36 | | 5x+30=2x+48 | | 4x^2-3x^3=0 | | X(x^2-9x)=0 | | .5x+7=14x+60 | | 1/2x+7=14x+60 | | .5x+7=14+60 | | 4m+8=6m-10 | | 1/2x+7=14+60 | | 3x+16=4x-8 | | 9x/26 | | X(x^2-4)=0 | | 5x+12=1x+8 | | 2xsquared-5x=0 | | 25=2x/2-5 | | 2x^3+x^2-x=0 | | 3x-(6x+5)=2x-15 | | x/2-1=9 | | 1/5x-1=7/10 | | 2x+2=2(x)-3(x+2) | | 4(5y-3)=25 | | 19x+500=200x | | 88000x+33=34x(54+4) | | f(x)=5x^2+40 | | 3.14=15y | | 179-2x=43x+19 |